(untitled) (Revista Argentina de Musicología, 2018)
This work is a partial result of an ongoing investigation, which in turn is linked with previous research, all dedicated to addressing a basic problem: the conflicting relationship between the audience and the most radical of contemporary musical art productions, as electroacoustic music, for example. Assuming that under the assumption that the problem lies the issue of taste, its conformation, its conditions and its targets, and after previous research addressed instances of reception (study of the relationship of the public with electroacoustic music) , and mediation/circulation (radial diffusion studies on academic discourse on music and specialized in daily review), in what could be called “critical program” to contribute to a questioning of musical taste as eminently conservative and traditionalist, this work is the description of the reproductive matrix: the concert, the first link in the chain in which the relative permanencechange in regard to the establishment of the register is combined with valuations, appraisals and reactions condition, in feedback, future programming. From this, a description of the concerts programming in the cities of Buenos Aires and La Plata between 2010 and 2013 is proposed.